Gendered differences in AIDS and AIDS-related cause of death among youth with secondary education in South Africa, 2009-2011 - Nicole De Wet (Taylor & Francis Group, 2016)
Background: The prevalence of human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) is higher among females than males in Sub-Saharan Africa. Education is associated with better health outcomes. For this and other reasons, African countries have made a concerted effort to increase youth education rates. However, in South Africa males have lower secondary education rates than females, yet females have a higher prevalence of HIV/AIDS. This study examines if a gender disparity exists in AIDS mortality rates among youth with secondary education in South Africa. Methods: This study uses descriptive statistics and life table techniques. A sample of 4386 deaths of youth with secondary education is used. Of this total sample, 987 deaths were among males and 340 were among females with secondary education. Results: This study shows that AIDS mortality is higher among females than males in South Africa. Males and females with secondary education have lower AIDS mortality than all males and females in the population, yet the rates are higher for females. Using cause-deleted life tables, the probability of youth dying from HIV/AIDS practically disappears for both males and females. Odds ratio calculations show that secondary education does not have a protective effect from AIDS mortality among male and female youth. Conclusion: Given the gendered difference in AIDS mortality among youth with secondary education, efforts to increase secondary education among males and further research into other factors exacerbating AIDS mortality among females with secondary education is needed in the country.